Making Flowers in Paper, Fabric and Ribbon - Biddle, Steve and Biddle, Megumi (London BCA, 1993)
All that is needed to create these displays bringing life, colour and style to your home, is a little imagination and instruction from the authors. They show step-by-step how to assemble and wire paper and fabric flowers for arrangements for the table, bouquets, to decorate gifts. Life size templates are provided.
Include Illustration and Index
Keywords: Artificial flowers -- Paper flowers -- Ribbon flowers